Constitutive Expression of Adiponectin in Endothelial Progenitor Cells Protects a Rat Model of Cerebral Ischemia - Liu, Yumin; Wang, Meiyao; Feng, Hongliang; Yu, Qing; Xie, Xiaorui; Zhang, Renwei; Li, Yan (Journal of neural transplantation & plasticity, 2017)
Endothelial progenitor cells (EPCs), as precursors to endothelial cells, play a significant part in the process of endogenous blood vessel repair and maintenance of endothelial integrity. Adiponectin (APN) is an adipocyte-specific adipocytokine. In this study, we aim to test whether we transplant a combined graft of EPCs transfected with the adiponectin gene into a rat model of cerebral ischemia could improve functional recovery after middle cerebral artery occlusion (MCAO). Sprague-Dawley (SD) rats were randomly divided into a MCAO control group, a MCAO EPC treatment group, and a MCAO LV-APN-EPC treatment group. A focal cerebral ischemia and reperfusion model was induced by the intraluminal suture method. After 2 h of reperfusion, EPCs were transplanted by injection through the tail vein. A rotarod test was conducted to assess behavioral function before MCAO and on days 1, 7, and 14 after MCAO. After 14 d, TTC staining, CD31 immunofluorescence, and TUNEL staining were used to evaluate infarct volume, microvessel density, and cell apoptosis. Results revealed that behavioral function, infarct area percentage, microvessel density, and cell apoptosis rates were more favorable in the LV-APN-EPC treatment group than in the EPC treatment group. These data suggested that gene-modified cell therapy may be a useful approach for the treatment of ischemic stroke.